Faktor Yang Mempengaruhi Berat Badan Bayi Yang Mengkonsumsi Susu Formula - Astarini, Made Indra Ayu; Juwita, Linda; Koryanti, Glory (JURNAL NERS LENTERA, 2021)
Introduction The weight of infants aged 0-6 months is an indicator of infant health. Weight gain is due to the food intake given. The main food for infant is breast milk. However, other reasons, breast milk must be replaced by formula milk where the carbohydrate and protein content is quite high which will affect the baby's weight. The purpose of this study was to determine the factors that affect the weight of infants who consume formula milk. Method The design of this research was cross sectional. The population was 30 respondents of infants aged 0-6 months in the working area of the Tenggilis Mejoyo Public Health Center. Sampling technique with total sampling so that the sample size was the same as the population. Statistical test used linear regression. Results There are 2 factors that affect the current weight of babies who consume formula milk, age (p = 0.003, R2 = 0.277) and the volume of milk given in a day (p = 0.001, R2 = 0.572). Discussion Giving formula milk in large volumes can increase infant's weight very quickly because the carbohydrate and protein content in formula milk is higher than breast milk. Older infant is heavier than younger infant. Conclusion Age and volume of milk given affect the baby's current weight.